Respostas

A melhor resposta!
2014-06-20T10:25:47-03:00
Bem, vamos aplicar o teorema:

(x+r)^2=(x-r)^2+x^2 \\  x^{2} +2xr+r^2=x^2-2xr+r^2+x^2 \\ x^2-2x^2+4xr=0 \\ -x^2+4xr=0 \\ x(-x+4r)=0 \\ -x+4r=0 \\ \\  \boxed{ x=4r}

Vamos substituir os valores agora.

A=\dfrac{x\cdot (x-r)}{2} \\ 300=x^2-xr \\ 300=16r^2-4r^2 \\ 12r^2=300 \\ r^2=25 \\  \\ \boxed{r=5}

Como x=4r
x=4×5
x=20

As medidas:

a=x+r \\ a=20+5 \\ \boxed{a=25} \\  \\  \\ b=x \\ \boxed{b=20} \\  \\  \\ c=x-r \\ c=20-5 \\ \boxed{c=15}


1 5 1